From modernism to postmodernism : concepts and strategies of postmodern American fiction - Hoffmann, Gerhard, 1931-2018 (Rodopi, 2005)
This systemic study discusses in its historical, cultural and aesthetic context the postmodern American novel between the years of 1960 and 1980. A general overview of the various definitions of postmodernism in philosophy, cultural theory and aesthetics provides the framework for the inquiry into more specific problems, such as: the broadening of aesthetics, the relationship between aesthetics and ethics, the transformation of the artistic tradition, the interdependence between modernism and postmodernism, and the change in the aesthetics of fiction. Other topics addressed here include: situa.
Keywords: American fiction -- 20th century -- History and criticism.; American fiction -- 21st century -- History and criticism.; Modernism (Literature) -- United States.; Postmodernism (Literature) -- United States.; Roman américain -- 20e siècle -- Histoire et critique.; Roman américain -- 21e siècle -- Histoire et critique.; Modernisme (Littérature) -- États-Unis.; Postmodernisme (Littérature) -- États-Unis.; LITERARY CRITICISM -- American -- General.; American fiction; Modernism (Literature); Postmodernism (Literature); United States; Modernisme (cultuur); Postmodernisme.; Amerikaans.; Fictie.; 1900-2099; Criticism, interpretation, etc.